2019
DOI: 10.56093/ijas.v89i3.87594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of planting density on growth, yield and quality of strawberry (Fragaria × ananassa) cv. Camarosa

Abstract: An investigation was carried out at experimental field, Department of Horticulture, Aromatic and Medicinal Plants, Mizoram University to study the effect of planting density on growth, yield and quality of strawberry(Fragaria ×ananassaa Duch.) cv. Camarosa. The experiment comprises of a number of planting densities, viz. T1: 50 × 40 cm,T2 : 40 × 40 cm, T3 : 40 × 30 cm, T4 : 30 × 30 cm, T5: 30 × 25 cm, T6 : 25 × 25 cm, T7 : 25 × 20 cm and T8 : 20 × 20 cm and T8 : 20 × 20 cm. Among the different planting density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Maximum total sugar (6.38%) and reducing sugar (5.61%) under silver black mulch might be attributed to high soil temperature and higher nutrient availability which provided favourable microclimate for increased sugar content. The current findings are in consonance with results of [24] who got total sugars (8.50%), reducing sugar (4.78%) in strawberry under wider spacing and [25] reported total sugar (5.71%), reducing sugar (3.41%), non-reducing sugar (2.30%) in aonla.…”
Section: Effect Of Crop Management Practices On Biochemical Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…Maximum total sugar (6.38%) and reducing sugar (5.61%) under silver black mulch might be attributed to high soil temperature and higher nutrient availability which provided favourable microclimate for increased sugar content. The current findings are in consonance with results of [24] who got total sugars (8.50%), reducing sugar (4.78%) in strawberry under wider spacing and [25] reported total sugar (5.71%), reducing sugar (3.41%), non-reducing sugar (2.30%) in aonla.…”
Section: Effect Of Crop Management Practices On Biochemical Parameterssupporting
confidence: 91%
“…Higher titratable acidity (0.74%) was obtained under closer spacing of 20 cm × 30 cm and 30 cm × 30 cm whereas minimum titratable acidity (0.71%) was recorded under wider spacing of 40 cm × 60 cm which might be due to shade effect where sugar conversion from organic acid is hampered due to lack of sufficient light in closer spacing. Least titratable acidity (0.65%) was found in silver black mulch and red mulch which might be due to rapid conversion of organic acid to sugars and more reflection of photosynthetically active radiation(PAR) from plastic mulch into fruiting zone elevated conversion into sugars and reduction of acidity [24] obtained lowest titrable acidity (0.812%) under wider spacing of 50 cm × 40 cm and [26] reported least acidity (1.40%) in plants under black polyethylene film and higher acid content (1.52%) under unmulched plants during his study on plum. Perusal of data revealed that the maximum ascorbic acid (78.65 mg 100 g −1 ) was recorded in 40 cm × 60 cm was at par with 40 cm × 40 cm mg 100 g −1 ) whilst the minimum ascorbic acid was recorded in 20 cm × 30 cm (67.30 mg 100 g −1 ).…”
Section: Effect Of Crop Management Practices On Biochemical Parametersmentioning
confidence: 99%
“…Higher fruit setting in plant under wider spacing might be due to greater photosynthetic activity because of exposure of more number of leaves to sunlight, while availability of poor sunlight to the lower leaves of the plant at closer spacing becomes a limiting factor and adversely affects the flowering and fruiting. Research results are in accordance with the findings of [10,46,47,48].…”
Section: Days From First Flower Opening To Fruit Settingsupporting
confidence: 91%
“…This might have helped in production of higher leaf area by producing wider leaves in wider spacing and narrow leaves in closer spacing. These results were supported by findings [8,9,10,11].…”
Section: Leaf Areasupporting
confidence: 88%